2016
DOI: 10.5213/inj.1632776.388
|View full text |Cite
|
Sign up to set email alerts
|

Current Opinion on the Role of Neurogenesis in the Therapeutic Strategies for Alzheimer Disease, Parkinson Disease, and Ischemic Stroke; Considering Neuronal Voiding Function

Abstract: Neurological diseases such as Alzheimer, Parkinson, and ischemic stroke have increased in occurrence and become important health issues throughout the world. There is currently no effective therapeutic strategy for addressing neurological deficits after the development of these major neurological disorders. In recent years, it has become accepted that adult neural stem cells located in the subventricular and subgranular zones have the ability to proliferate and differentiate in order to replace lost or damaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 102 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…For instance, microglia‐like cells have been generated from iPSC in vitro (Pandya et al, ; Muffat et al, ), indicating that reduced resident microglial cells in AD brain might be replenished by transplanted stem cells. Moreover, it is well established that the widespread loss of neurons strongly correlates with deficient neurogenesis in AD (Han, Lee, & Koh, ), and one study has demonstrated that anti‐inflammatory cytokines released by microglia could promote endogenous neurogenesis in AD mice (Kim J. A., et al, ), suggesting that stem cell therapies would boost neurogenesis through immunomodulation.…”
Section: Microglial Response To Transplanted Stem Cells In Ad Micementioning
confidence: 99%
“…For instance, microglia‐like cells have been generated from iPSC in vitro (Pandya et al, ; Muffat et al, ), indicating that reduced resident microglial cells in AD brain might be replenished by transplanted stem cells. Moreover, it is well established that the widespread loss of neurons strongly correlates with deficient neurogenesis in AD (Han, Lee, & Koh, ), and one study has demonstrated that anti‐inflammatory cytokines released by microglia could promote endogenous neurogenesis in AD mice (Kim J. A., et al, ), suggesting that stem cell therapies would boost neurogenesis through immunomodulation.…”
Section: Microglial Response To Transplanted Stem Cells In Ad Micementioning
confidence: 99%
“…In the last years, the role of neurogenesis as a therapeutic strategy for neurodegenerative diseases has been investigated [5,54]. The adult brain is capable of generating new neurons from self-renewing and multipotent adult neuronal stem cells in the dentate gyrus in order to replace lost or damaged neuronal cells.…”
Section: Other Targets: Neurotrophic Factors and Neurogenesismentioning
confidence: 99%
“…Its incidence is between 10 and 50/100 000 person per year, with a prevalence between 100 and 300/100 000 population. Both incidence and prevalence increase progressively after 60 years of age [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Compelling evidence has established that neural stem cells (NSCs) exert a substantial beneficial and therapeutic effect after transplantation in experimental neurodegeneration disease models. NSCs repair damaged tissue not only by physically replacing cells but also by secreting neurotrophic or immune modulatory factors [ 14 , 15 ]. In oxygen-deprived conditions, NSCs constitutively produce and secrete neurotrophic factors and hormones, such as nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 99%